Application of Factorial Design Experiments to the Development of a Disposable Amperometric DNA Biosensor - Uliana, Carolina Venturini [UNESP]; Tognolli, Joao Olimpio [UNESP]; Yamanaka, Hideko [UNESP] (Wiley-v C H Verlag Gmbh, 2011)
The development of an amperometric DNA-based biosensor (genosensor) requires the optimization of many experimental parameters in order to maximize sensitivity. If only one parameter is evaluated per experiment, the resultant genosensor is unlikely to be ideal, because several of the parameters could be interdependent. Herein, chemometric experiments employing full and fractional factorial designs were used to develop biosensor for hepatitis. The results demonstrate that the use of chemometric tools enables optimization of experimental conditions using a smaller number of experiments and with reduced requirements for reagents and samples, which is in line with the principles of green chemistry.
Keywords: Chemometrics; DNA; Factorial design; Genosensor; Hepatitis C virus